The design of social and cultural orientated urban tissues through evolutionary processes. (September 2021) - Choi, Jason; Nguyen, Phat Chi Thanh; Makki, Mohammed
The research examines how social and cultural properties can be utilised as an alternative planning scheme to improve urban morphology and enhance the overall experience of individuals within the city. The aim is for these socio-cultural properties to be translated into quantitative data sets that define the morphological characteristics of the urban tissue. Through the use of evolutionary optimisation methods, the process of urban growth is simulated through a series of individuals that adapt and optimise for multiple design criteria. The experiment presented quantifies the social and cultural properties of a superblock within the city of Kyoto to generate an urban tissue that is susceptible to future growth.